A (tidal-marine) boulder pavement in the late Cenozoic of Seymour Island, West Antarctica: contribution to the palaeogeographical and palaeoclimatic evolution of West Antarctica. Issue 6 (7th September 2017) - Rocha-Campos, Antonio C.; Kuchenbecker, Matheus; Duleba, Wania; Dos Santos, Paulo Roberto; Canile, Fernanda M.
Abstract: We report here the discovery of a boulder pavement cropping out at the base of the Hobbs Glacier Formation (Miocene), on the northern sector of Seymour Island (Isla Marambio), West Antarctica, along the contact with the underlying La Meseta Formation (Eocene). The feature described has many points in common with boulder pavements developed in tidal-marine environments. The clasts of the pavement are mostly boulders and bear up to three sets of glacial striae on their bevelled truncated surfaces, but are not elongate parallel to them or bullet shaped. No diamictite body was identified associated with the boulder pavement. These features differ from those of boulder pavements described from terrestrially glaciated Cenozoic deposits and may indicate a shallow glaciomarine environment for the late Cenozoic of Seymour Island.